Моделі релігійної освіти молодших школярів у країнах Європейського Союзу - Ярова, Олена (Studies in Comparative Education, 2014)
У статті розглянуто принципи та підходи до організації релігійної освіти молодших школярів у державах-членах Європейського Союзу. Автор аналізує практику релігійної освіти на рівні МСКО 1 і характеризує основні моделі РО – конфесійну (або деномінаційну) та неконфесійну (або релігієзнавчу). Визначено спільні для країн ЄС риси та виклики в організації РО на початковому щаблі. В статье рассматриваются принципы и подходы к организации религиозного образования младших школьников в государствах-членах Европейского Союза. Автор анализирует практику религиозного образования на уровне МСКО 1 и характеризует основные модели РО – конфессиональную (или деноминационную) и неконфессиональную (или религиоведческую). Определены общие для стран ЕС черты и проблемные моменты в организации РО на начальной ступени. The article examines the principles and approaches to religious education of younger schoolchildren in the Member States of the European Union. The author analyzes the practice of religious education at ISCED level 1 and characterizes its main models: confessional (or denominational) and non-confessional. The difference between the two models is determined by their content, the system of teacher training, curriculum development and teaching provision for which either the state or religious associations are responsible. The article identifies the common features and challenges in the organization of religious education at the primary stage, among which are the voluntariness of the students’ choice in this field, the possibility of studying religious culture of some particular denomination or non-religious ethics, the negotiation of RE content with representatives of religions, indicating the general trend of Europeanization. The author comes to the conclusion that the practice of religious education in the Member States of the European Union is greatly dependent on complex specifics of each country. The implementation of existing models of RE is facing numerous challenges due to the recent changes in the social context of Europe. Recognizing the need and usefulness of international consultations and cooperation in the field of RE, religious scholars and teachers point out such difficulties as language issue, the problem of cultural and language barriers, and differences in the existing educational systems. The gradual transition from the confessional model of teaching school religion to the non-confessional one allows to acquaint students with a variety of world religions, strengthens the developmental function of RE, and focuses on Ecumenical and interreligious education for mutual understanding and respect for other religious traditions and worldview.